Positive electrode for lithium secondary battery and lithium secondary battery comprising same

By adopting a multi-layer structure design in the positive electrode of the lithium secondary battery, combining lithium transition metal oxides with layered and olivine structures, the conductivity and wettability of the LFP-based positive electrode active material is solved, and the energy of the battery is improved Density and stability.

CN119208521APending Publication Date: 2024-12-27SK ON CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410826374.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-27
Filing Date
2024-06-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The LFP-based positive electrode active substance has problems such as low conductivity, low lithium ion diffusion coefficient and poor wettability of the electrolyte in lithium secondary batteries, resulting in reduced battery performance and unstable capacity retention.

Method used

A multi-layer positive electrode structure is adopted, wherein the first positive electrode mixture layer comprises a lithium transition metal composite oxide of a layered structure, and the second positive electrode mixture layer comprises a lithium transition metal oxide of an olivine structure, and is adjusted by adjusting the thickness ratio and conductivity of both. agent content to improve conductivity and wettability.

Benefits of technology

It improves the energy density and conductivity of the battery, reduces the resistance, solves the initial capacity hump phenomenon and battery safety problems, and ensures the high stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208521A_ABST
    Figure CN119208521A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode for a lithium secondary battery and a lithium secondary battery comprising the same, and provides a positive electrode comprising: a current collector; a first positive electrode mixture layer formed on at least one surface of the current collector; and a second positive electrode mixture layer formed on the first positive electrode mixture layer, in which the first positive electrode mixture layer includes a first positive electrode active material having a layered crystal structure, and the second positive electrode mixture layer includes a second positive electrode active material having an olivine-based crystal structure, the first positive electrode mixture layer and the second positive electrode mixture layer have a thickness ratio of 1: 9 to 4: 6.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a positive electrode for a lithium secondary battery and a lithium secondary battery comprising the positive electrode. Background Art

[0002] Due to the increase in the use of portable electronic devices and environmental issues such as CO2 emissions caused by the use of fossil fuels, the popularity of electric vehicles using secondary batteries as a power source has rapidly progressed, resulting in a sharp increase in demand for secondary batteries. As this demand increases, the demand for high capacity and high safety of secondary batteries has also increased.

[0003] In the global automotive battery market, when the positive electrode is classified according to the positive electrode active material used for lithium secondary batteries, it can be roughly listed as NCM-based positive electrodes using lithium nickel cobalt manganese oxide as the positive electrode active material and LFP-based positive electrodes using lithium iron phosphate (LFP), lithium iron manganese phosphate (LFMP) and the like as the positive electrode active material.

[0004] Among them, the LFP-based positive electrode active material used for the LFP-based positive electrode is characterized in that it has a stable olivine structure, and the structure does not change during the insertion and extraction process of lithium ions, and has excellent high-temperature cycle performance and safety.

[0005] Therefore, lithium iron phosphate positive electrode active material is a positive electrode material with high safety, and by using it as a positive electrode active material of the positive electrode, it can help ensure the high safety of lithium secondary batteries. However, the LFP-based positive electrode active material has the limitations of low electrical conductivity and low lithium ion diffusion coefficient.

[0006] In addition, the LFP-based positive electrode containing the LFP-based positive electrode active material has low electrolyte wettability, so the supply of electrons is not smooth and it is difficult for the electrolyte to penetrate into the positive electrode mixture layer. Figure 1 As shown, a hump phenomenon occurs. When this hump phenomenon occurs, the initial battery cell cannot show the maximum performance, and in terms of capacity, there is a problem that the maximum capacity held by the battery cannot be used until the capacity retention rate stabilizes.

[0007] Figure 1 is a graph showing the change in capacity retention rate of a positive electrode using an LFP-based positive electrode active material according to cycles, as shown in Figure 1 As shown, the characteristic is that the capacity does not reach 100% at the beginning, but a phenomenon of slow increase (hump phenomenon) occurs.

[0008] Furthermore, the positive electrode mixture layer using the LFP-based positive electrode active material has low binding force with the positive electrode current collector, thereby causing an increase in resistance, and thus there is a problem of reduced cell performance. Summary of the invention

[0009] Technical issues to be solved

[0010] As a specific embodiment of the present invention, an object thereof is to improve the problem of low energy density in a positive electrode containing an LFP-based positive electrode active material while maintaining high safety of the battery by using an LFP-based positive electrode active material.

[0011] In addition, as another specific embodiment of the present invention, an object thereof is to improve the conductivity by improving the wettability of the electrolyte in the positive electrode containing the LFP-based positive electrode active material and to enhance the adhesion with the positive electrode current collector in the lithium secondary battery.

[0012] Technical Solution

[0013] According to the present invention, a positive electrode is provided, which includes: a current collector; a first positive electrode mixture layer formed on at least one side of the current collector; and a second positive electrode mixture layer formed on the first positive electrode mixture layer, wherein the first positive electrode mixture layer contains a first positive electrode active material having a layered crystal structure, and the second positive electrode mixture layer contains a second positive electrode active material having an olivine-based crystal structure, and the first positive electrode mixture layer and the second positive electrode mixture layer have a thickness ratio of 1:9 to 4:6.

[0014] The first positive electrode active material may be a lithium transition metal composite oxide represented by Chemical Formula 1.

[0015] [Chemical formula 1]

[0016] Li a Ni x Co y Mn z M 1 w O2

[0017] In the chemical formula 1, M 1 is at least one selected from Al, Mg, V, Ti and Zr, 0.9≤a≤1.5, 0.5≤x<1, 0 <y≤0.4,0<z≤0.4,0<w≤0.04,x+y+z+w=1。

[0018] The second positive electrode active material may be a lithium transition metal oxide represented by Chemical Formula 2.

[0019] [Chemical formula 2]

[0020] LiMPO4

[0021] In the chemical formula 2, M is at least one selected from Fe, Mn, Ni, Co and V.

[0022] The second positive electrode mixture layer may further include a first positive electrode active material.

[0023] The second positive electrode mixture layer may include 0.5-30 wt % of the first positive electrode active material relative to the total weight of the positive electrode active material including the first positive electrode active material and the second positive electrode active material in the entire positive electrode mixture layer including the first positive electrode mixture layer and the second positive electrode mixture layer.

[0024] The content of the second positive electrode active material contained in the entire positive electrode mixture layer including the first positive electrode mixture layer and the second positive electrode mixture layer may be 50 wt % or more relative to the total weight of the positive electrode active material including the first positive electrode active material and the second positive electrode active material.

[0025] The second positive electrode mixture layer may include a linear conductive agent having an aspect ratio of 2 or more.

[0026] The linear conductive agent may be contained in an amount of 1 to 10 wt % relative to the total weight of the second positive electrode mixture layer.

[0027] The second positive electrode mixture layer may include a linear conductive agent, wherein the linear conductive agent is a carbon nanotube; a carbon fiber; or at least one metal fiber selected from the group consisting of copper, nickel, aluminum, and silver.

[0028] The first positive electrode mixture layer may further include at least one conductive agent selected from carbon fiber, carbon nanotube, graphite, carbon black (acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black), metal fiber, metal powder, conductive whisker, conductive metal oxide and conductive polymer.

[0029] The content of the conductive agent may be 1 to 10 wt % relative to the total weight of the first positive electrode mixture layer.

[0030] At least one of the first positive electrode mixture layer and the second positive electrode mixture layer may further include a third positive electrode active material in addition to the first positive electrode active material and the second positive electrode active material.

[0031] The third positive electrode active material may be selected from Li2MnO3, Li2PtO3, LiMn2O4 and LiNi 0.5 Mn 1.5 At least one of O4.

[0032] As another aspect, according to a specific embodiment, there is provided a lithium secondary battery in which negative electrodes and positive electrodes are alternately stacked and a separator is provided between the negative electrodes and the positive electrode, the positive electrode being the positive electrode as described above.

[0033] Beneficial Effects

[0034] The positive electrode according to the present invention includes an NCM-based positive active material having high capacity characteristics, thereby improving low conductivity, low adhesion to a positive current collector, and low wettability to an electrolyte that the LFP-based positive active material has.

[0035] Therefore, by using the positive electrode of the present invention, the resistance of the battery cell can be improved while including the LFP-based positive electrode active material, and the hump problem of the initial capacity can be solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a graph showing the change in capacity retention rate according to cycles of a positive electrode using an LFP-based positive electrode active material.

[0037] Figure 2 is a diagram schematically showing a cross section of a positive electrode according to a specific embodiment of the present invention.

[0038] Figure 3 is a graph showing voltage change and temperature change measured for the positive electrode according to Example 1.

[0039] Figure 4 3 is a graph showing voltage change and temperature change measured for the positive electrode according to Comparative Example 1.

[0040] Figure 5 The graphs are graphs comparing the voltage change and temperature change over time of the positive electrode of Example 1, the positive electrode of Comparative Example 1, and the positive electrode of Comparative Example 2 including NCM as a positive electrode active material.

[0041] Description of Reference Numerals

[0042] 3: Positive electrode current collector

[0043] 5: First positive electrode mixture layer

[0044] 6: Second positive electrode mixture layer

[0045] 7: Positive electrode mixture layer

[0046] 10: Positive electrode DETAILED DESCRIPTION

[0047] The present invention relates to a positive electrode for a lithium secondary battery and a lithium secondary battery including the positive electrode. More specifically, the present invention aims to improve the problems of a positive electrode containing an LFP-based positive electrode active material as a positive electrode material while maintaining the safety of the battery.

[0048] The positive electrode active material of the olivine structure is composed of hexahedrons, so the stability of the lattice structure is very high. Even if lithium ions are intercalated and deintercalated during discharge, there is little deterioration of the crystal structure, so the life stability is high.

[0049] However, the disadvantages of the positive electrode active material of the olivine structure are low conductivity, slow diffusion rate of lithium ions, and low energy density. In addition, the positive electrode active material of the olivine structure has poor wettability to the electrolyte, so the electrolyte has low impregnation into the positive electrode. In addition, the positive electrode active material of the olivine structure also has low adhesion to the electrode current collector.

[0050] In addition, in the layered lithium transition metal compound, the constituent elements constituting the positive electrode active material are located in the layered structure, and when the battery is charged, lithium ions are stored between the layers of the wide and flat crystal lattice, so a large amount of lithium ions can be stored, thereby having a high energy capacity. In addition, such a layered transition metal compound generally has excellent wettability to the electrolyte, so that the lithium ions impregnated from the positive electrode surface can easily reach the inside of the positive electrode.

[0051] Therefore, a specific embodiment of the present invention can provide a positive electrode, which improves the problems of low conductivity, slow lithium ion diffusion rate and electrolyte wettability of the positive electrode active material with an olivine structure while ensuring the safety of the positive electrode.

[0052] As a specific embodiment, a positive electrode is provided, which includes the positive electrode active material having an olivine structure as described above and a positive electrode active material having a layered structure as the positive electrode active material.

[0053] As an example, the positive electrode according to the present invention is a multilayer positive electrode including a first positive electrode mixture layer and a second positive electrode mixture layer on at least one side of a positive electrode collector. Figure 2 2 shows a cross section of an exemplary positive electrode according to the present invention.

[0054] like Figure 2 As shown, the positive electrode 10 according to the present invention includes: a positive electrode collector 3; a first positive electrode mixture layer 5, which is formed on one side or both sides of the positive electrode collector 3 and contains a first positive electrode active material; and a second positive electrode mixture layer 6, which is formed on the first positive electrode mixture layer 5 and contains a second positive electrode active material.

[0055] In the present invention, the second positive electrode mixture layer 6 formed on the first positive electrode mixture layer 5 may be directly formed on and in contact with the first positive electrode mixture layer 5. In addition, in the present invention, another layer may be provided between the first positive electrode mixture layer 5 and the second positive electrode mixture layer 6.

[0056] Specifically, in the positive electrode 10 provided by the present invention, a first positive electrode mixture layer 5 is formed on the positive electrode current collector 3, and the first positive electrode mixture layer 5 contains a lithium transition metal compound having a layered structure in the crystal lattice structure as the first positive electrode active material, and a second positive electrode mixture layer 6 is formed on the first positive electrode mixture layer 5, and the second positive electrode mixture layer 6 contains a lithium transition metal compound having an olivine structure in the crystal lattice structure as the second positive electrode active material.

[0057] In the present invention, by including a layered positive active material in the first positive electrode mixture layer 5 formed on the positive electrode collector 3, the adhesion of the positive electrode mixture layer 7 to the positive electrode collector 3 can be improved, thereby reducing the resistance at the interface between the positive electrode collector 3 and the positive electrode mixture layer 7. In addition to improving this adhesion, by locating the layered positive active material with better conductivity near the positive electrode collector 3, the conductivity can be improved.

[0058] Moreover, by having a layered positive electrode active material with good wettability with the electrolyte, the electrolyte that penetrates from the positive electrode surface to the inside can more easily penetrate near the positive electrode collector, and this improvement in electrolyte wettability can further contribute to improving conductivity.

[0059] As described above, the positive electrode of the present invention may include a positive electrode mixture layer containing an olivine-based positive electrode active material to ensure the safety of the positive electrode, and may include a positive electrode mixture layer containing a layered positive electrode active material inside the positive electrode, i.e., on the positive electrode collector side, to improve the electrical properties of the positive electrode.

[0060] In the positive electrode 10 of the present invention, the second positive electrode mixture layer 6 may be thicker than the first positive electrode mixture layer 5. Specifically, the first positive electrode mixture layer 5 and the second positive electrode mixture layer 6 may have a thickness ratio of 1:9 to 4:6, more specifically, 1.5:8.5 to 4:6, 2:8 to 4:6, or 2.5:7.5 to 3.5:6.5.

[0061] When the thickness ratio of the first positive electrode mixture layer 5 to the second positive electrode mixture layer 6 is not within the above range and the thickness of the first positive electrode mixture layer 5 is thinner, the loading amount of the first positive electrode mixture layer 5 becomes too small, and thus the wettability of the electrolyte to the entire positive electrode 10 cannot be sufficiently improved, so that the electrolyte may not smoothly penetrate into the first positive electrode mixture layer 5 located on the positive electrode current collector 3 side, and thus the improvement such as Figure 1 The effect of the hump phenomenon is shown.

[0062] In addition, when the thickness ratio of the first positive electrode mixture layer 5 and the second positive electrode mixture layer 6 is not within the above range and the thickness of the first positive electrode mixture layer 5 is thicker, the thickness of the second positive electrode mixture layer 6 becomes thinner, so it may be difficult to ensure the battery safety brought about by the second positive electrode mixture layer 6. For example, during battery driving, due to gas generation inside the battery cell, etc., a sharp rise in battery temperature and ignition may occur, and battery performance may be deteriorated, such as a sharp drop in voltage.

[0063] The layered transition metal compound may be represented by the general formula LiMO2, for example, wherein M may include at least one transition metal element such as Ni, Co, and Mn.

[0064] The layered structured transition metal compound may be, for example, a monolithic lithium transition metal oxide containing one of the transition metal elements, and may be a binary lithium transition metal composite oxide containing two of the transition metal elements, and may be a ternary lithium transition metal composite oxide containing Ni, Co and Mn as transition metal elements as constituent elements.

[0065] Specifically, the layered transition metal compound may be composed of Li a Mn 1-x M 1 x A2.Li a Mn 1-x M 1 x O 2-y X y , Li a Mn2O 4-z X y , Li a Mn 2-x M 1 x M 2 y A4, Li a Co 1-x M 1 x A2.Li a Co 1-x M 1 x O 2-y X y , Li a Ni 1-x M 1 x A2.Li a Ni 1-x M 1 x O 2-y X y , Li a Ni 1-x Co x O 2-y X y , Li a Ni 1-x-y Co x M 1 y A2.Li a Ni 1-x-y Co x M 1 y O 2-z X z , Li a Ni 1-x-y Mn x M 1 y A z or Li a Ni 1-x- y Mn x M 1 y O 2-z X z Represents the compound.

[0066] In the chemical formulas, M 1 and M 2 are the same or different from each other and are each independently selected from Mg, Al, Co, K, Na, Ca, Si, Ti, Sn, Ge, Ga, B, As, Zr, Mn, Cr, Fe, Sr, V and rare earth elements, A is selected from O, F, S and P, X is selected from F, S and P, 0.9≤a≤1.5, 0≤x≤0.5, 0≤y≤0.5, 0≤z≤2.

[0067] More specifically, the layered transition metal compound may be a ternary transition metal compound, for example, may be a compound represented by the following Chemical Formula 1.

[0068] [Chemical formula 1]

[0069] Li a Ni x Co y Mn z M 1 w O2

[0070] In the chemical formula 1, M 1is at least any one selected from Al, Mg, V, Ti, and Zr, 0.9 ≤ a ≤ 1.5, 0.5 ≤ x < 1, 0 < y ≤ 0.4, 0 < z ≤ 0.4, 0 < w ≤ 0.04, and x + y + z + w = 1.

[0071] The a represents the molar ratio of lithium in the lithium transition metal oxide represented by the chemical formula 1. For example, it can be 1 ≤ a ≤ 1.5, 1 ≤ a ≤ 1.2, 1 ≤ a ≤ 1.15, or 1 ≤ a ≤ 1.10.

[0072] The x represents the molar ratio of nickel in the metal component other than lithium in the lithium transition metal oxide represented by the chemical formula 1, which can be 0.5 ≤ x < 1.0, or can be 0.6 ≤ x < 1.0 or 0.8 ≤ x < 1.0. The y represents the molar ratio of cobalt in the metal component other than lithium in the lithium transition metal oxide represented by the chemical formula 1, which can be 0 < y ≤ 0.4, or can be 0 < y ≤ 0.2. The z represents the molar ratio of manganese in the metal component other than lithium in the lithium transition metal oxide represented by the chemical formula 1, which can be 0 < z ≤ 0.4, or can be 0 < z ≤ 0.2. In addition, the w represents the molar ratio of the doping element M 1 in the metal component other than lithium in the lithium transition metal oxide represented by the chemical formula 1, which can be 0 < w ≤ 0.04, or can be 0 < w ≤ 0.02.

[0073] In the present invention, a second positive electrode mixture layer 6 is formed on the first positive electrode mixture layer 5, and the second positive electrode mixture layer 6 contains a positive electrode active material having an olivine structure in its crystal lattice structure. As described above, by forming a second positive electrode mixture layer containing an active material with an olivine structure on the first positive electrode mixture layer, high stability of the battery can be ensured, and the problem of reduced adhesion between the positive electrode active material with an olivine structure and the positive electrode current collector 3 can be improved, thereby reducing the interfacial resistance and improving the conductivity.

[0074] The positive electrode active material with an olivine structure can be a lithium transition metal oxide represented by the following chemical formula 2.

[0075] [Chemical formula 2]

[0076] LiMPO4

[0077] In the chemical formula 2, M can be at least one selected from Fe, Mn, Ni, Co, and V.

[0078] For example, the second positive electrode active material can be LiFePO4, LiMnFePO4, etc.

[0079] The second positive electrode mixture layer 6 may contain the first positive electrode active material while containing the second positive electrode active material. When the second positive electrode mixture layer 6 further contains the first positive electrode active material while containing the second positive electrode active material, the interface resistance between the first positive electrode mixture layer 5 and the second positive electrode mixture layer 6 can be reduced, thereby improving the conductivity, and the wettability of the electrolyte to the second positive electrode mixture layer 6 can be improved, and the capacity can be increased.

[0080] When the second positive electrode active material and the first positive electrode active material are mixed in the second positive electrode mixture layer 6, although not particularly limited, the content of the first positive electrode active material can be less than 50 weight %, for example, can be 0.5-30 weight %, relative to the total weight of the positive electrode active material including the first positive electrode active material and the second positive electrode active material in the entire positive electrode mixture layer 7 including the first positive electrode mixture layer 5 and the second positive electrode mixture layer 6.

[0081] At least one of the first positive electrode mixture layer 5 and the second positive electrode mixture layer 6 may further contain an additional positive electrode active material in addition to the first positive electrode active material and the second positive electrode active material. The additional positive electrode active material may include, but is not limited to, a spinel structured positive electrode active material. The spinel structured positive electrode active material may include, for example, lithium manganese oxide (LiMn2O4), lithium nickel manganese composite oxide (LiNi 0.5 Mn 1.5 O4), etc., more specifically, it may further contain lithium nickel manganese composite oxide (LiNi 0.5 Mn 1.5 O4). The lithium nickel manganese composite oxide as described above has a high energy density of 650 W·h / kg and a high operating voltage of about 4.7 V compared to lithium, thereby offsetting the disadvantages of the second positive electrode active material and contributing to further improving the stability of LFP.

[0082] In addition, a lithium transition metal compound (oxide) represented by the general formula Li2MO3 may be included as an additional positive electrode active material. Wherein, M may include at least one of transition metal elements including Mn, Fe, Co, and Pt, for example, Li2MnO3 and Li2PtO3 may be listed. Moreover, other metal elements or non-metal elements may be further included.

[0083] When at least one of the first positive electrode mixture layer 5 and the second positive electrode mixture layer 6 further contains the additional positive electrode active material (third positive electrode active material), the content of the third positive electrode active material can be appropriately selected within the range of maintaining the content of the second positive electrode active material above 50 weight %, for example, it can be 0.5-30 weight %.

[0084] Moreover, at least a portion of the third positive electrode active material may have a coating on the surface. The coating may contain at least one coating element compound selected from oxides, hydroxides, oxyhydroxides, oxidized carbonates and basic carbonates of the coating element. The coating element contained in the coating may use Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr or a mixture thereof. The coating element compound forming the coating may be amorphous or crystalline.

[0085] The first positive electrode mixture layer 5 and the second positive electrode mixture layer 6 may include a binder for bonding the positive electrode active materials in the positive electrode mixture layers and bonding the positive electrode mixture layer 7 and the positive electrode current collector 3 .

[0086] The binder may be any binder commonly used in the positive electrode mixture layer without particular limitation, and for example, polyvinyl alcohol, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, acrylic-based rubber, etc. may be used.

[0087] More specifically, in the second positive electrode mixture layer 6, acrylic-based rubber such as polyacrylic acid (PAA), polymethylmethacrylate, polyisobutylmethacrylate, polyethylacrylate, polybutylacrylate, polyethylhexylacrylate (poly(2-ethylhexylacrylate))) can be used as a binder.

[0088] The content of the binder contained in the first positive electrode mixture layer 5 and the second positive electrode mixture layer 6 may be independently 0.5-10 wt % relative to the weight of each positive electrode mixture layer. More specifically, the content of the binder may be 0.5 wt % or more, 0.8 wt % or more, 1 wt % or more, 1.2 wt % or more, or 1.5 wt % or more, and may be 10 wt % or less, 7 wt % or less, 5 wt % or less, 4 wt % or less, 3 wt % or less, or 2 wt % or less.

[0089] The first positive electrode mixture layer 5 and the second positive electrode mixture layer 6 may also each independently contain a thickener. The thickener may be a cellulose-based compound, for example, carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, cellulose diacetate or an alkali metal salt thereof, and the alkali metal may be Na, K or Li. As for the binder, the first positive electrode mixture layer 5 may contain one binder as described above, or may contain two or more binders as described above.

[0090] The content of the thickener contained in the first positive electrode mixture layer 5 and the second positive electrode mixture layer 6 may be independently 0.1-3 wt % relative to the weight of each positive electrode mixture layer. For example, the content of the thickener may be 0.1 wt % or more, 0.3 wt % or more, 0.5 wt % or more, or 0.6 wt % or more, and may be 3 wt % or less, 2.5 wt % or less, 2 wt % or less, 1.5 wt % or less, or 1.2 wt % or less.

[0091] The first positive electrode mixture layer 5 and the second positive electrode mixture layer 6 may each independently contain a conductive agent. The conductive agent is not particularly limited as long as it is a conductive material commonly used in the positive electrode 10 of the secondary battery. The same conductive agent may be used, and different types may be used depending on the positive electrode active material used in each positive electrode mixture layer.

[0092] For example, the second positive electrode mixture layer 6 may include a linear conductive agent as the second conductive agent. Compared with a point-type conductive agent, the linear conductive agent has higher conductivity and can more easily achieve connection between the olivine-based positive active materials included in the second positive electrode mixture layer 6, thereby improving the conductivity of the olivine-based positive active materials.

[0093] The linear conductive agent has a shape in which the length is longer than the thickness. For example, a conductive agent having an aspect ratio of 2 or more can be cited. Specifically, a conductive agent having an aspect ratio of 2 or more, 3 or more, 5 or more and 600 or less, 300 or less, 100 or less, 50 or less, or 20 or less can be cited. More specifically, the linear conductive agent can include carbon fibers, carbon nanotubes (CNTs), metal fibers such as copper, nickel, aluminum, and silver, and any one of them can be used, and two or more of them can be mixed and used. More specifically, carbon fibers and carbon nanotubes can be cited.

[0094] The content of the linear conductive agent may be 1-10 wt % relative to the weight of the second positive electrode mixture layer 6. When the content of the linear conductive agent is less than 1 wt %, the positive electrode active material may not be easily bonded to the current collector, and when the content of the linear conductive agent exceeds 10 wt %, the capacity of the electrode may be reduced.

[0095] The first conductive agent contained in the first positive electrode mixture layer 5 is not particularly limited, and may contain a linear conductive agent as described above, and may also contain a dot conductive agent.

[0096] The point-type conductive agent may be, for example, a conductive agent having an aspect ratio of 0.5 to 1.5, and may be substantially spherical. Examples of the point-type conductive agent include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; metal powders such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives.

[0097] The content of the first conductive agent contained in the first positive electrode mixture layer 5 may be 1-10 wt % relative to the weight of the first positive electrode mixture layer 5, but is not limited thereto. When the content of the first conductive agent is less than 1 wt %, the adhesion between the positive electrode active material and the current collector is insufficient, and when the content of the first conductive agent exceeds 10 wt %, the capacity of the electrode may be reduced.

[0098] The positive electrode 10 according to the present invention can be manufactured by mixing the positive active material, binder, conductive agent and solvent as described above to prepare positive electrode mixture slurry, and coating the positive electrode mixture slurry on the positive electrode collector 3 to manufacture the positive electrode 10 .

[0099] The solvent is not particularly limited, and not only water-based solvents such as water can be used, but also non-aqueous solvents can be used. The non-aqueous solvent can also be used in the present invention as long as it is a solvent commonly used in preparing the positive electrode mixture slurry of the secondary battery, for example, dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water can be cited, but it is not limited thereto.

[0100] The positive electrode current collector 3 is a metal with good conductivity, for example, aluminum, nickel, titanium, stainless steel, etc., and can be in various forms such as sheet, foil, mesh, etc. The thickness of the positive electrode current collector 3 is not particularly limited, for example, it can be 5-30 μm.

[0101] As described above, the positive electrode mixture slurry is applied on at least one side of the positive electrode collector as described above, and dried and rolled, so that a positive electrode having a positive electrode mixture layer formed on the positive electrode collector can be manufactured.

[0102] More specifically, a first positive electrode mixture slurry containing a first positive electrode active material may be coated on the positive electrode current collector, and a second positive electrode mixture slurry containing a second positive electrode active material may be coated. The second positive electrode mixture slurry may be coated simultaneously with the first positive electrode mixture slurry, or the second positive electrode mixture slurry may be coated continuously after the first positive electrode mixture slurry is coated, or the second positive electrode mixture slurry may be coated after a certain time interval.

[0103] In addition, a drying step of removing the solvent while applying the positive electrode mixture slurry or after a certain time interval may be included. In the drying step, the second positive electrode mixture slurry may be applied after drying the first positive electrode mixture slurry, and the first positive electrode mixture slurry and the second positive electrode mixture slurry may be dried simultaneously.

[0104] The drying method is not particularly limited, and a drying method commonly used in electrode drying can be applied. For example, various drying methods such as natural drying, heating drying, reduced pressure drying and air drying can be listed, and the drying can be divided into multiple steps of two or more steps.

[0105] At this time, the drying method is not particularly limited, and thus a conventional drying method may be applied. For example, various drying methods such as natural drying, heating drying, reduced pressure drying, and air drying may be used, and the drying may be performed in a plurality of steps.

[0106] A calendering process may be performed after the drying process, and the thickness and density of the positive electrode mixture layer may be adjusted by the calendering process. The calendering may be performed by conventional methods such as a roller pressing method and a flat pressing method. The thickness of the positive electrode mixture layer obtained by the calendering process is not particularly limited, for example, it may be greater than 20 μm and less than 200 μm, specifically, it may be greater than 30 μm, greater than 40 μm, greater than 60 μm, greater than 80 μm or greater than 100 μm, and may be less than 200 μm, less than 180 μm, less than 160 μm, less than 150 μm or less than 120 μm.

[0107] In addition, the density of the positive electrode mixture layer can be controlled by the calendering process. Although not particularly limited, for example, in order to improve battery power, life and high-temperature storage characteristics, the density of the positive electrode mixture layer can be 1.2 g / cm 3 More specifically, the density of the positive electrode mixture layer may be 1.2 g / cm 3 Above or 1.5g / cm 3 Above, and can be 2.2g / cm 3 Below, 2.1g / cm 3 Below or 2.0g / cm 3 the following.

[0108] The multilayer positive electrode provided by the present invention as described above can improve the safety of the battery by including an olivine-structured positive electrode active material such as LFP, and by forming a positive electrode mixture layer including a layered structured positive electrode active material such as NCM on the positive electrode collector side, the adhesion with the positive electrode collector, the wettability of the electrolyte and the conductivity can be improved, thereby improving the battery performance.

[0109] The present invention can provide a lithium secondary battery, the lithium secondary battery comprising the positive electrode according to the present invention. Specifically, the positive electrode and the negative electrode according to the present invention are alternately stacked with the separator as the boundary to manufacture an electrode assembly, and then the electrode assembly is inserted into a battery case and sealed, and an electrolyte is injected, so that a lithium secondary battery can be provided.

[0110] The negative electrode may be manufactured by coating a negative electrode mixture slurry including a negative electrode active material, a binder, and a solvent, and including a conductive agent and a thickener as needed, on a negative electrode current collector, and performing drying and rolling.

[0111] The negative electrode active material may be a carbon-based negative electrode active material. The carbon-based negative electrode active material can be appropriately used in the present invention as long as it is a material commonly used in manufacturing the negative electrode of a secondary battery, and thus is not particularly limited, but may include crystalline carbon-based active materials such as artificial graphite and natural graphite. The artificial graphite or natural graphite may be amorphous, plate-shaped, flaky, spherical, fibrous, or a combination thereof.

[0112] As the negative electrode active material, artificial graphite and natural graphite may be included alone or a mixture of artificial graphite and natural graphite may be included. When the artificial graphite and natural graphite are mixed, the mixing ratio may be 70:30 to 95:5 by weight. In addition, the artificial graphite can further improve the dispersibility of the slurry and can improve the life and high-temperature storage characteristics.

[0113] In addition, the negative electrode active material may include at least one of a silicon (Si)-based negative electrode active material, a tin (Sn)-based negative electrode active material, or a lithium vanadium oxide negative electrode active material, and such a negative electrode active material can be used together with the carbon-based negative electrode active material. When the non-carbon-based negative electrode active material as described above is mixed with the carbon-based negative electrode active material, the content of the non-carbon-based negative electrode active material may be in the range of 1-50% by weight based on the total weight of the negative electrode active material.

[0114] The Si-based negative electrode active material may be Si, a Si-C composite, SiO x (0 < x < 2), or a Si-Q alloy. In the Si-Q alloy, Q may be an element other than Si and selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof. Specifically, it may be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0115] Generally, it is known that Si-based negative electrode active materials as negative electrode active materials have the characteristic of large volume change. Therefore, generally, a silicon-based negative electrode active material can be added and included together with a carbon-based negative electrode active material such as graphite. At this time, carbon nanotubes can be included as a conductive agent in terms of preventing swelling caused by the volume expansion of the silicon-based negative electrode active material.

[0116] The Sn-based negative electrode active material may be Sn, SnO2, or Sn-R alloy. In the Sn-R alloy, R may be an element other than Sn and Si, selected from alkali metals, alkaline earth metals, elements of Group 13, elements of Group 14, elements of Group 15, elements of Group 16, transition metals, rare earth elements, and combinations thereof, specifically, may be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof. In addition, at least one of them may be mixed with SiO2 for use.

[0117] The content of the negative electrode active material in the negative electrode mixture layer may be 94-98 wt % relative to the total weight of the negative electrode mixture layer.

[0118] The conductive agent is used to impart conductivity to the electrode, and any conductive agent commonly used in secondary batteries may be used without restriction, for example, carbon-based substances such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, etc.; metal-based substances such as metal powders or metal fibers such as copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or conductive materials containing mixtures thereof.

[0119] The content of the conductive agent may be 0.1 to 3 wt % relative to the total weight of the negative electrode mixture layer.

[0120] The binder binds the negative electrode active material particles to each other and binds the negative electrode active material to the negative electrode current collector. The binder may be a water-based binder, but is not limited thereto.

[0121] The water-based adhesive can include styrene-butadiene rubber (SBR), acrylated styrene-butadiene rubber, nitrile rubber, acrylic rubber, butyl rubber, ethylene-propylene copolymer, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, ethylene-propylene diene monomer rubber, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol resin, acrylate-based resin or a combination thereof.

[0122] The content of the binder may be 1.5-3 wt % relative to the total weight of the negative electrode mixture layer.

[0123] The thickener is used to impart viscosity, and the thickener may be a cellulose-based compound, for example, a mixture of one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or alkali metal salts thereof, etc. The alkali metal may be Na, K, or Li.

[0124] The thickener may be used in an amount of 0.1 to 3 parts by weight relative to 100 parts by weight of the negative electrode active material.

[0125] As the solvent, an aqueous solvent such as water can be used.

[0126] In the present invention, the negative electrode current collector may use at least one selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, and a combination thereof.

[0127] The thickness of the negative electrode current collector is not particularly limited, and may be, for example, 5-30 μm.

[0128] As described above, the negative electrode mixture slurry is coated on one or both sides of the negative electrode current collector and dried and rolled to manufacture a negative electrode having a negative electrode mixture layer formed on the negative electrode current collector. At this time, the negative electrode mixture layer may be a single layer, two layers, or three layers or more.

[0129] The drying and rolling for producing the negative electrode mixture layer can be performed by the same method as the production of the positive electrode mixture layer described above, and thus a detailed description is omitted.

[0130] Example

[0131] The present invention will be described in more detail below by way of examples. The following examples are provided to illustrate the present invention, but the present invention is not limited to the following examples.

[0132] Example 1

[0133] Based on the solid weight, 95 wt % of NCM622 positive electrode active material, 2 wt % of polyvinylidene fluoride (PVDF) binder and 3 wt % of carbon black conductive agent were mixed with NMP solvent to prepare slurry for forming the first positive electrode mixture layer.

[0134] Based on the solid weight, 95 wt % of LFP positive electrode active material, 2 wt % of polyacrylic acid binder and 3 wt % of carbon black conductive agent were mixed with NMP solvent to prepare slurry for forming the second positive electrode mixture layer.

[0135] The slurry for forming the first positive electrode mixture layer was applied on both sides of an aluminum foil (thickness: 12 μm) as a positive electrode current collector and dried. Next, the slurry for forming the second positive electrode mixture layer was applied on the first positive electrode mixture layer, dried, and then rolled.

[0136] Thereby, a positive electrode having the first positive electrode mixture layer and the second positive electrode mixture layer is manufactured.

[0137] The thickness of the prepared positive electrode was 200 mm, and the thicknesses of the first positive electrode mixture layer and the second positive electrode mixture layer had a ratio of 3:7.

[0138] Comparative Example 1

[0139] A positive electrode was manufactured by the same method as in Example 1 except that the thickness ratio of the first positive electrode mixture layer to the second positive electrode mixture layer was adjusted to 5:5.

[0140] Comparative Example 2

[0141] The same positive electrode having a thickness of 10 mm was manufactured using the slurry for forming the first positive electrode mixture layer.

[0142] Evaluation of physical properties

[0143] -Electrode capacity-

[0144] The capacities of the positive electrodes manufactured in Example 1, Comparative Example 1 and Comparative Example 2 were measured, and were 47Ah, 47.7Ah and 71Ah, respectively. It can be seen that although the content of NCM positive electrode active material in the entire positive electrode of Example 1 is less than that of Comparative Example 1, it has a similar capacity to Comparative Example 1.

[0145] - Changes in voltage and temperature inside the positive electrode -

[0146] For the positive electrodes manufactured in Example 1, Comparative Example 1 and Comparative Example 2, the changes in voltage and temperature were measured by the following method, and the results are shown in Figures 3 to 5 middle.

[0147] Voltage change: Connect wires to the positive and negative terminals to measure the voltage of the battery cell, and confirm whether the battery cell vents and catches fire as the voltage of the battery cell drops.

[0148] Temperature change: A heating pad is placed in contact with the main body of the battery cell and current is applied to heat the battery cell, and a temperature sensor is used to measure the temperature change of the battery cell caused by the heating.

[0149] Figure 3 The voltage change and temperature change of the positive electrode manufactured in Example 1 are shown in FIG. Figure 4Graphs 2 and 3 show the voltage change and temperature change of the positive electrode manufactured in Comparative Example 1.

[0150] exist Figure 3 and Figure 4 In the case of a battery cell, a drop in voltage indicates that the battery cell is damaged due to outgassing or fire in the battery cell. Figure 4 It can be seen that the voltage of the positive electrode of Comparative Example 1 drops before 5 minutes have passed. Figure 3 As shown, the positive electrode of Example 1 showed a result that the voltage dropped after 5 minutes, and thus the voltage was maintained for a longer time than that of Comparative Example 1.

[0151] From the above Figure 3 and Figure 4 It can be seen that the positive electrode of Example 1 did not catch fire and maintained the voltage for a longer time, thus ensuring better battery stability. However, in the positive electrode of Comparative Example 1, the thickness of the first positive electrode mixture layer using NCM as the positive electrode active material was formed thicker, so the capacity increase effect was not shown, and it caught fire in a short time, causing a sharp drop in voltage, so it was confirmed that the battery safety was poor.

[0152] It can be seen that, like the positive electrode of Example 1, by adjusting the thickness ratio of the first positive electrode mixture layer to the second positive electrode mixture layer, the performance of the positive electrode can be further improved.

[0153] in addition, Figure 5 Graph showing changes in voltage and temperature of the positive electrodes of Example 1, Comparative Example 1, and Comparative Example 2 over time. Figure 5 In the figure, the voltage drop of the battery cell indicates that the battery cell is in a state where it cannot function due to exhaust or fire in the battery cell, and the positive electrode of Comparative Example 2 loses the function of the battery cell the fastest. Therefore, it can be seen that compared with the positive electrode of Comparative Example 2, the positive electrode of Example 1 and Comparative Example 1 containing LFP have better stability, and compared with the positive electrode of Comparative Example 1, the positive electrode of Example 1 has better stability, and it can be seen that as the LFP content increases, the battery cell maintains its function for a longer time, so it has high stability.

Claims

1. A positive electrode, comprising: current collector; a first positive electrode mixture layer formed on at least one side of the current collector; and a second positive electrode mixture layer formed on the first positive electrode mixture layer, The first positive electrode mixture layer comprises a first positive electrode active material having a layered crystal structure, and the second positive electrode mixture layer comprises a second positive electrode active material having an olivine-based crystal structure. The first positive electrode mixture layer and the second positive electrode mixture layer have a thickness ratio of 1:9 to 4:

6.

2. The positive electrode according to claim 1, wherein The first positive electrode active material is a lithium transition metal composite oxide represented by Chemical Formula 1: [Chemical formula 1] Li a Ni x Co y Mr z M 1 w O2 In the chemical formula 1, M 1 is at least one selected from Al, Mg, V, Ti and Zr, 0.9≤a≤1.5,0.5≤x<1,0 <y≤0.4,0<z≤0.4,0<w≤0.04,x+y+z+w=1。 3. The positive electrode according to claim 1, wherein The second positive electrode active material is a lithium transition metal oxide represented by Chemical Formula 2: [Chemical formula 2] LiMPO4 In the chemical formula 2, M is at least one selected from Fe, Mn, Ni, Co and V.

4. The positive electrode according to claim 1, wherein The second positive electrode mixture layer further includes a first positive electrode active material.

5. The positive electrode according to claim 4, wherein The second positive electrode mixture layer contains 0.5-30 wt % of the first positive electrode active material relative to the total weight of the positive electrode active material including the first positive electrode active material and the second positive electrode active material in the entire positive electrode mixture layer including the first positive electrode mixture layer and the second positive electrode mixture layer.

6. The positive electrode according to claim 4, wherein The content of the second positive electrode active material contained in the entire positive electrode mixture layer including the first positive electrode mixture layer and the second positive electrode mixture layer is 50 wt % or more relative to the total weight of the positive electrode active material including the first positive electrode active material and the second positive electrode active material.

7. The positive electrode according to claim 1, wherein The second positive electrode mixture layer includes a linear conductive agent having an aspect ratio of 2 or more.

8. The positive electrode according to claim 7, wherein The content of the linear conductive agent is 1 to 10 wt % relative to the total weight of the second positive electrode mixture layer.

9. The positive electrode according to claim 1, wherein The second positive electrode mixture layer comprises a linear conductive agent, wherein the linear conductive agent is a carbon nanotube; a carbon fiber; and at least one metal fiber selected from copper, nickel, aluminum and silver.

10. The positive electrode according to claim 1, wherein The first positive electrode mixture layer further includes at least one conductive agent selected from the group consisting of carbon fibers, carbon nanotubes, graphite, carbon black, metal fibers, metal powders, conductive whiskers, conductive metal oxides, and conductive polymers.

11. The positive electrode according to claim 10, wherein The carbon black includes acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black.

12. The positive electrode according to claim 10, wherein The content of the conductive agent is 1 to 10 wt % relative to the total weight of the first positive electrode mixture layer.

13. The positive electrode according to any one of claims 1 to 12, wherein At least one of the first positive electrode mixture layer and the second positive electrode mixture layer further includes a third positive electrode active material in addition to the first positive electrode active material and the second positive electrode active material.

14. The positive electrode according to claim 13, wherein The third positive electrode active material is selected from Li2MnO3, Li2PtO3, LiMn2O4 and LiNi 0.5 Mn 1.5 At least one of O4.

15. A lithium secondary battery in which negative electrodes and positive electrodes are alternately stacked and a separator is provided between the negative electrodes and the positive electrodes, The positive electrode is the positive electrode according to any one of claims 1 to 14.

Citation Information

Cited By

  • Secondary battery and electronic device

    CN120978075A